2020
DOI: 10.1093/infdis/jiaa066
|View full text |Cite
|
Sign up to set email alerts
|

A Protein Epitope Targeted by the Antibody Response to Kawasaki Disease

Abstract: Background Kawasaki disease (KD) is the leading cause of childhood acquired heart disease in developed nations and can result in coronary artery aneurysms and death. Clinical and epidemiologic features implicate an infectious cause but specific antigenic targets of the disease are unknown. Peripheral blood plasmablasts are normally highly clonally diverse but the antibodies they encode are approximately 70% antigen-specific 1–2 weeks after infection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 47 publications
3
31
0
3
Order By: Relevance
“…A recent study from South Korea reported no temporal association of human coronavirus infection and incidence of Kawasaki disease at the national level (23). Recent research progress supports a presently unidentified so-called new respiratory RNA virus as the cause of the disease (24).…”
Section: Discussionmentioning
confidence: 96%
“…A recent study from South Korea reported no temporal association of human coronavirus infection and incidence of Kawasaki disease at the national level (23). Recent research progress supports a presently unidentified so-called new respiratory RNA virus as the cause of the disease (24).…”
Section: Discussionmentioning
confidence: 96%
“…Physicians have noted some clinical similarities between MIS-C and Kawasaki disease (KD), a febrile illness of young childhood involving inflammation of the blood vessels that can result in coronary artery aneurysms. KD is presently of unknown aetiology, although substantial recent progress supports a presently unidentified ubiquitous virus as the cause 6 . Patients with MIS-C may have some of the clinical features of KD, including fever, dilation of conjunctival blood vessels, rash and redness of the oropharynx.…”
mentioning
confidence: 99%
“…A peptide recognized by antibodies produced during the acute phase of Kawasaki disease has been identified in 2020 (reF. 52 ). Although the protein epitopes seem similar to hepaciviruses 53 , further studies are required to determine the specific gene sequence from which this peptide emerges.…”
mentioning
confidence: 99%